Analisis Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan di PT. XYZ - Tarmizi, Akmal; Qohar, Muhammad Fikri Bivani Al; Bagus , Ujang; Andriani, Aulia; Agustiyani, Noppy; Illahi, Muhamad Rizki Nur; Rahma, Rana Ardila (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Organizational culture greatly influences the behavior of organizational members because the value system in organizational culture can be used as a reference for human behavior in an organization that is oriented towards achieving set goals or performance results, so that if the organizational culture is good, it is not surprising that organizational members are good and qualified people as well. This study aims to analyze the effect of organizational culture on employee performance at PT XYZ. This research was conducted using a quantitative approach and collecting data from employees who work in the company. The results of data analysis show that organizational culture has a positive and significant effect on employee performance at PT XYZ because the t test results in this study found that the organizational culture variable has a t count of 5.629, while the t table value has a value of 2.006. Where t count> t table then, Ha is accepted and Ho is rejected